Deskripsi Kesalahan Mahasiswa dalam Menyelesaikan Soal Geometri Analitik Menurut Teori Newman Ditinjau dari Kemampuan Matematika - Asmaun, Asmaun; Arwadi, Fajar; Rifandi, Muh. (Universitas Cokroaminoto Palopo, 2025)
Analytical geometry as a course that involves algebraic processes in solving problems requires students' accuracy and it is not uncommon for various errors to occur due to the varying levels of students' mathematical abilities. This study aims to describe students' errors in solving Analytical Geometry problems according to Newman's theory as viewed from their mathematical abilities. This research is a qualitative study with a descriptive approach. This research was conducted at the Mathematics Department, Faculty of Mathematics and Natural Sciences, Makassar State University in the even semester of 2023/2024. The subjects in this study were students of the Mathematics Department consisting of 3 people, namely students with high mathematical abilities, students with moderate mathematical abilities, and students with low mathematical abilities. The sampling technique used was purposive sampling by setting criteria for selecting research subjects. Data were collected through written tests and interviews. As well as data analysis techniques used qualitatively by collecting data, presenting data and drawing conclusions. The results obtained in this study were that the errors made by students with high mathematical abilities only made mistakes in the reading and endcoding processes, while at other stages according to Newman's theory, students did not make mistakes and were able to get the correct answers. Students with moderate mathematical abilities make reading errors, comprehension errors, transformation errors, process skill errors and endcoding errors. Students with low mathematical abilities make errors at every stage, at the reading stage, students also do not understand the meaning of the question (comprehension) so that students are unable to use the correct notation (transformationi) and ultimately are unable to continue the solution process.